Gemcitabine and capecitabine with or without telomerase peptide vaccine GV1001 in patients with locally advanced or metastatic pancreatic cancer (TeloVac): an open-label, randomised, phase 3 trial - Middleton, Gary; Silcocks, Paul; Cox, Trevor; Valle, Juan; Wadsley, Jonathan; Propper, David; Coxon, Fareeda; Ross, Paul; Srinivasan, Madhusudan; Roques, Tom; Cunningham, David; Falk, Stephen; et al. (Elsevier, 2014)
BACKGROUND: We aimed to assess the efficacy and safety of sequential or simultaneous telomerase vaccination (GV1001) in combination with chemotherapy in patients with locally advanced or metastatic pancreatic cancer.